2005
DOI: 10.1158/1055-9965.epi-05-0239
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Apoptosis, and Colorectal Adenoma Risk

Abstract: Compelling evidence from epidemiologic studies indicates that elevated circulating insulin-like growth factor (IGF)-I, insulin resistance, and associated complications, such as elevated fasting plasma insulin, glucose and free fatty acids, glucose intolerance, increased body mass index, and visceral adiposity, are linked with increased risk of colorectal cancer. However, the role of insulin and markers of glucose control in the development of adenomas, precursors to colorectal cancer, has not been fully explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 68 publications
(88 reference statements)
6
111
2
Order By: Relevance
“…The association of insulin and the IGF axis with colorectal adenoma has been investigated in at least 10 studies to date. 10,[16][17][18][19][20][21][22][23][24] Nevertheless, all were conducted in only three countries, the United States, the United Kingdom and Japan, and significant associations were mainly reported in the former two countries. This discrepancy is probably best explained as the sum of several differences in demographic characteristics between Japan and the other two countries including genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of insulin and the IGF axis with colorectal adenoma has been investigated in at least 10 studies to date. 10,[16][17][18][19][20][21][22][23][24] Nevertheless, all were conducted in only three countries, the United States, the United Kingdom and Japan, and significant associations were mainly reported in the former two countries. This discrepancy is probably best explained as the sum of several differences in demographic characteristics between Japan and the other two countries including genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are only two studies of colorectal neoplasia in which circulating levels of these biomarkers were investigated for men and women separately in the same study settings, albeit both studies did not find any association in either men or women. 9,10 Further, no meta-analysis has been conducted for men and women separately to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria included colitis (either ulcerative, Crohn's, radiation or infectious colitis, chronic inflammatory illnesses), previous colonic or small bowel resection, previous colon adenomas or colon cancer, sigmoidoscopy or incomplete colonoscopies, familial polyposis syndrome. The enrollment procedure as well as colonoscopy and biopsy procedures are similar to previously described protocols (Keku et al, 2005;Shen et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…IR is an established risk factor for patients with hepatocellular carcinoma (HCC) due to the hypoxic and ischemic conditions encountered during tumor progression. Several studies revealed that IR was a prognostic factor for the postoperative recurrence of HCC (Yoshikawa et al, 2001;Keku et al, 2005;Soliman et al, 2006;Turati et al, 2013). However, the specific mechanism of IR and its relationship with multidrug resistance are unclear.…”
Section: Introductionmentioning
confidence: 99%